Electropolymerization polyaniline-reduced graphene oxide for oer electrode - Aloycius, Chua Chun Hoe (2025)
Nowadays, green energy is becoming a trend in society as a step towards sustainable and environmentally friendly energy sources. One promising approach to generating green energy is through the electrochemical splitting of water, where water molecules are broken down into hydrogen and oxygen using electrolysis. To evaluate the efficiency of this process, oxygen evolution reaction tests must be conducted. The materials used in this process should have good conductivity to achieve maximum efficiency. In this study, graphene and polyaniline were chosen as the main materials, with graphene sheets coated in polyaniline. To investigate the electrochemical performance of these materials, physicochemical studies and characterizations were carried out using instruments such as Fourier Transform Infrared (FTIR), Scanning Electron Microscopy (SEM), and Autolab potentiostat. Electrochemical tests were performed at specific scan rates for Electrochemical Impedance Spectroscopy (EIS), cyclic voltammetry (CV), and linear sweep voltammetry (LSV) at rates of 10, 50, and 100 mV/s. Additionally, scan rates of 5 to 30 mV/s were used for ECSA testing with a 1M KOH electrolyte solution. The results indicated that PANI/rGO/GCE exhibited better performance compared to rGO/GCE. This was demonstrated through the highest current density obtained from the LSV voltammogram as well as lower solution resistance identified through Nyquist ECSA plots. Data showed that polyaniline performed exceptionally well after the electropolymerization of rGO/GCE, with improvements in the electrical conductivity of single sheets and a large surface area of rGO. These findings highlight significant potential for water-splitting applications in producing more efficient green energy. Overall, this study emphasizes the importance of using materials like graphene and polyaniline to enhance the efficiency of water-splitting processes for green energy production. With outstanding performance following electropolymerization, these materials offer new hope in the quest for clean and renewable energy sources.